Impact of COPD case finding on clinical care: a prospective analysis of the TargetCOPD trial. Issue 10 (5th October 2020) - Haroon, Shamil; Adab, Peymane; Dickens, Andrew P; Sitch, Alice J; Rai, Kiran; Enocson, Alexandra; Fitzmaurice, David A; Jordan, Rachel E
Abstract : Objectives: To investigate the impact of chronic obstructive pulmonary disease (COPD) case finding on clinical care. Design: We conducted a prospective observational analysis of data from a pragmatic cluster randomised controlled trial in primary care in the West Midlands, UK (TargetCOPD). This compared alternative methods of COPD case finding against usual care. Data were extracted from electronic healthcare records and self-reported questionnaires for a subset of patients with newly diagnosed COPD. Setting: 50 general practices that participated in the TargetCOPD trial. Participants: Patients aged 40–79 years newly identified with COPD by targeted case finding or by usual care, from 10 August 2012 to 22 June 2014. Primary and secondary outcome measures: The primary outcome was addition to a COPD register by the end of the trial. The secondary outcome was a clinical care score, derived from the sum of clinical assessments and relevant interventions. Associations between participant characteristics and the primary and secondary outcomes were assessed using multilevel regression. Results: 857 patients identified with COPD by case finding and 764 by usual care were included. Only 21.2% of case-found patients had been added to a COPD register, compared with 92.7% of those diagnosed by usual care. The odds of being added were greater in smokers (adjusted OR 8.68, 95% CI 2.53 to 29.8), and in those with lower percentage of predicted forced expiratory volume in 1 s (adjusted OR 0.96 per percentage rise, 95% CI 0.95 to 0.98). Patients who had been added to a COPD register had a significantly higher clinical care score (mean difference 5.06, 95% CI 4.36 to 5.75). Conclusions: Only one in five case-found patients had been registered with COPD. Patients added to a COPD register received significantly higher levels of appropriate clinical care. Trial registration number: ISRCTN14930255 ; Post-results.